A cryptography method employing a new mathematical paradigm for public keys schemes - Ribeiro, Vinicius Gadis (2004)
blic Keys Schemes usually generate two pairs of keys that bear some mathematical relation-usually, a relation of the field known as Number Theory. Identifying a key from another that is given is a problem of great difficulty. This paper presents a public key scheme in wich such key identification is also a great difficulty problem-however, the mathematical problem does not fall under Number Theory; rather, it is one of Differential equations, the rules of Lie groups being the best solution. Even using Lie groups, a problem of great difficulty still remains. The first few examples use Maple 5.0, a symbolic processing program, and are available in an Internet site.